Properties of mortar containing ceramic powder waste as cement replacement - Samadi, M.; Hussin, M.; Seung Lee, H.; Mohd Sam, A.; Ismail, Mohamed; Abdul Shukor Lim, N.; Ariffin, N.; Nur, N. (2015)
© 2015 Penerbit UTM Press. All rights reserved. Ceramic materials are largely used in all over the world and consequently, large quantities of wastes are produced simultaneously by tile manufacturers and construction industry. Nevertheless, part of these wastes and those produced by the construction industry are dumped in landfills. This paper presents the effect of using ceramic waste in mortar as cement replacement. Four mortar mixes were prepared in this study and focuses on the effect of ceramic powder as cement replacement on the strength development and the morphology of the mortar. The microstructural characteristics of the mortar were investigated by scanning field emission electron microscopy (FESEM) and the mineralogical properties was investigated using the X-ray diffraction (XRD). The cement was replaced by ceramic powder from 0% to 60% by weight of cement. The specimens were cast in 50 × 50 × 50 mm cube and water curing regime was used until the age of testing. The fineness of ceramic powder used is less than 45µm. The developments of compressive strength were studied for all samples. It is found that the optimum replacement that gave the highest strength was 40% replacement. It was also found that the use of ceramic powder enhanced the microstructure and strength properties of the mortar.